Risk Factors and Outcome of Patients with Obstetric Anal Sphincter Injuries (OASIS) - Bhatt, Rabindra D.; Sitaula, S.; Pradhan, T.; Manandhar, T.; Basnet, T. (Journal of BP Koirala Institute of Health Sciences, 2018)
Background: Anal incontinence is an embarrassing condition that is largely underreported. Obstetric anal sphincter injuries are the most important etiological factors. Anal sphincter injury during delivery is considered to be one of the major risk factors for fecal incontinence in women. After anal sphincter injury at the time of delivery, up to 50% women have complaints of fecal incontinence, mainly because of persisting sphincter defects. Objectives: To evaluate the risk factors for the occurrence of obstetric anal sphincter injuries during vaginal delivery. To evaluate the outcome of patients with obstetric anal sphincter injuries. Methodology: A retrospective descriptive study was conducted from 2014 to 2016. Data of all patients with Obstetric Anal Sphincter Injuries (OASIS) over 3 years was collected from the medical record section after ethical clearance from Institutional Review Committee (IRC), BPKIHS. The data was entered in the excel sheet and analyzed using SPSS 17. Results: The Most important risk factor of OASIS was operative vaginal delivery (vacuum assisted vaginal delivery), followed by birth weight of the baby greater than 3.5 Kg and primigravida. Conclusion: Patients undergoing operative vaginal delivery, primigravida and birth weight greater than 3 kg are the important risk factors for OASIS. So, patients with these conditions should be handled carefully during second stage of labor to prevent the occurrence of OASIS.